PROBLEMS AND PROSPECTS OF VACCINATION AGAINST INFLUENZA AMONG RISK GROUPS IN PREGNANT WOMEN AND STUDENTS' OF THE URGENCH BRANCH OF TMA (ResearchJet Journal of Analysis and Inventions, 2021)
In this work, the awareness of students about the course of influenza was investigated. The attitude of students to influenza vaccination in pregnant women and students was analyzed. Influenza does not lose its relevance at the present time, causing the development of local outbreaks, epidemics in different regions of the world, where, despite the availability of effective immunoprophylaxis, death of patients from this nosological form is noted. Unfavorable outcomes are reported among the unvaccinated categories. In our opinion, adherence to this preventive measure among target risk groups (students and pregnant women) is important.